Upaya Peningkatkan Keaktifan dan Hasil Belajar Siswa dengan Menggunakan Model Pembelajaran Project Based Learning - Wulandari, Isti Citra (PT. Media Edukasi Borneo, 2024)
The purpose of this study was to describe the implementation of the Project Based Learning (PBL) in improving the learning activities and outcomes of elementary school students in Tebedak, Landak. The research employed classroom action research (CAR) model of John Elliot, starting with planning activities that had previously obtained class event data in the form of problems that occur and had been identified, general planning of the entire cycle to be carried out. The next activity was the implementation or action of research, at the action or implementation stage, the observation or monitoring process was conducted. The results of the study showed that the score of student activity and learning outcomes experienced a significant increase between the value of student learning activity in cycle I learning of 52.42 and cycle II learning of 85.36. Then the means score of student learning outcomes in cycle I was 38.33 and cycle II was 80.90. It can be concluded that the PBL learning model is very effective in improving student activity and learning outcomes. ABSTRAK Tujuan penelitian ini adalah mendeskripsikan implementasi model Project Based Learning (PBL) dalam meningkatkan keaktifan dan hasil belajar siswa sekolah dasar di Tebedak, Landak. Metode penelitian yang digunakan adalah penelitian tindakan kelas (PTK) model John Elliot, diawali dengan kegiatan perencanaan yang terlebih dahulu sudah diperoleh data peristiwa kelas berupa permasalahan yang terjadi dan sudah teridentifikasi, perencanaan bersifat umum dari keseluruhan siklus yang akan dilakukan. Kegiatan berikutnya adalah pelaksanaan atau tindakan penelitian, pada tahap tindakan atau pelaksanaan dilakukan proses pengamatan atau monitoring. Hasil penelitian menunjukkan nilai keaktifan dan hasil belajar siswa mengalami kenaikan yang signifikan antara nilai keaktifan belajar siswa pada pembelajaran siklus I sebesar 52, 42 dan pembelajaran siklus II sebesar 85, 36. Kemudian nilai hasil belajar siswa pada siklus I sebesar 38, 33 dan siklus II sebesar 80,90. Maka model pembelajaran PBL sangat efektif dalam meningkatkan keaktifan dan hasil belajar siswa. KATA KUNCI: Keaktifan, hasil belajar, PBL.